Implementasi Kebijakan Desentralisasi Menuju Masyarakat Mandiri Dan Sejahtera - I Wayan Sutrisna (Jurnal Ilmiah Cakrawarti, 2020)
Decentralization policy can actually bring this nation into two possibilities, namelychallenges and hopes. This means that if regional autonomy is well managed then it will bringsociety to progress, prosperity that is aspired together. This is caused by public participation willget a broad space. The people will be able to collect responsibility for welfare from their regionalheads. When this critical power and control gets stronger the emergence of the door to abuse ofpower can be prevented. But on the contrary if this is not managed properly it will be able tobring disaster to the community. As one component of accountability to the public, the RegionalGovernment is expected to be able to optimize spending carried out effectively and efficiently toachieve a better level of community welfare. The government carries out three main functions,namely the first function of allocation, namely the government allocates funds for economicresources in the form of goods or services. The second function is the distribution function,namely the function of the government in an effort to carry out equitable development, incomeand wealth, in order to reduce the level of inequality. The third function is the stabilizationfunction, which is the function of the government which includes defense of security, economyand monetary to maintain broad employment opportunities, price stability and economic growth.Planning will not be able to produce development in accordance with the aspirations of thecommunity if it cannot optimize community participation in the process of preparing the plan.Without utilizing community participation in a good and directed manner, the plans arrangedcannot be adjusted to the aspirations and wishes of the community. Community participation inthe preparation of the APBD must be given sufficient space so that community involvement inthe process of managing the regional budget is maximized so that it can improve the efficiencyand effectiveness of development. Decentralization policy by granting autonomous rights todistrict / city governments provides opportunities for regional governments to design andimplement policies which is indeed needed by the local community. Regional autonomy hasbrought the government closer to the community in terms of services and involvement in alldevelopment activities. The district / city government as an autonomous region has been givenwider authority to explore the potential of the region and to channel it to the interests of thecommunity to its full potential in realizing a prosperous society.